Evaluation of certain Nitrogen-Fixing Bacteria against Fusarium spp. infected peanut - Abdallah, A. R.; Aldahtory, Th. A.; El-Sheikh, M. M.; Abd-Elmagid, W M. A. (Journal of Phytopathology and Disease Management, 2016)
In this study, the inhibition of soil borne pathogenic fungi Fusarium spp. that cause root and pod rot diseases in peanut (Arachis hypogaea) was investigated by using soil-isolated Plant Growth Promoting Rhizobacteria (PGPR), (Azotobacter and Azospirillum) and root-nodule Brady- Rhizobium as biological agents. Twenty seven isolates of Azotobacter and 26 isolates of Azospirillum obtained from rhizosphere of peanut plants, The efficiency of the nitrogenase activity was estimated and the best four Azotobacter isolates including (A3, A7, A11, and A20) and three Azospirillum isolates including (AZ2, AZ14 and AZ18) were selected as the most efficient in nitrogenase activity. These isolates were subjected to test their ability in solubilizing zinc and phosphate and their strength in direct antagonism. The isolates A7 and Az18 were more efficient in solubilizing Phosphate and zinc. Azospirillum sp. AZ18, Azotobacter sp. A7 and Brady-Rhizobium sp. B-Rh1 achieved the highest reduction percentage in mycelia linear growth of pathogenic fungi in vitro. Under greenhouse conditions, Azotobacter sp. A7 recorded the highest disease reduction percentage of peanut root rot (44.38 %). Furthermore, Brady-Rhizobium sp. B-Rh1 recorded the highest disease reduction of peanut pod rot (50.6%) followed by Azotobacter sp. A7 (47.62%). In addition, our results showed that inoculation with the tested nitrogen fixing bacteria gave remarkable increase in the yield parameters of peanut plants such as number and weight of pods and increased the vegetative biomass overall.